Kesantunan Berbahasa Pada Komentar Postingan Akun Instagram Lambeturah - Erawati Erawati; Syahruddin Syahruddin; Arifuddin Arifuddin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This study aims to describe the form of language politeness in comments posted on the Lambeturah Instagram account. This research is descriptive qualitative. The data from this study is in the form of written language which contains elements of language politeness contained in the Lambeturah Instagram account which is then analyzed and studied based on studies that are in accordance with the focus of the research and the source of the data from this research is reader responses or comments on the Lambeturah Instagram account. The research results obtained in this study were as many as 29 data. Among them, there are 8 data of sympathy maxims, 6 data in the form of consensus maxim, 5 data in the form of appreciation maxim and 10 data in the form of wisdom maxim.